A TECNOLOGIA MÓVEL E OS POTENCIAIS DA COMUNICAÇÃO NA EDUCAÇÃO - Fedoce, Rosângela Spagnol (2011)
The research is based on three main axes, communication, education and digital technology, with an exploratory analysis on the market production of content for mobile media. The study is developed with a bibliographic review related to these three axes and the use of qualitative methodology. Semi-structured interviews are realized with representatives of the mobile communication market in the country with the goal to describe the flow of content production, focusing on possibilities for development of mobile learning. In this sense, the technological potentials and communicative use of new Information and Communication Technologies (ICTs) are verified, especially the cell phone, in formal and informal models of education, from aspects of the Knowledge Society, as media convergence, interactivity and collaborative production. It is observed trends such as the appreciation of the content in relation to the media and the development of new experiences of access to information through the use of mobile and converging technologies.